Study of Variability in the Results of the Marsh Cone and Mini-slump tests - Mahisbadwe Ashwini; Gettu R.; Jayasree C. (Research Data and Reports, 2026)
The flow behaviour of cement paste depends significantly on the type and dosage of the superplasticizer used. The Marsh cone and mini-slump tests of the cement paste are simple and easy tests for assessing the flow properties of cement paste. In this paper, the ability of these tests to replicate the results under constant execution conditions has been studied. The variability introduced by inherent random errors during the testing process has been quantified in terms of repeatability values for these tests. The test results confirmed good repeatability, indicating that the test methods are robust.